Cell adhesion on glassy scaffolds with a different mechanical response. Issue 4 (3rd January 2017) - Shimomura, Shinichiro; Matsuno, Hisao; Sanada, Kazuaki; Tanaka, Keiji
Abstract : Fibroblasts can sense the surface stiffness of polymeric bilayers depending on a mechanical response from the rubbery layer underneath. Abstract : L929 mouse fibroblast cells were cultured on bilayer films composed of a glassy poly(methyl methacrylate) (PMMA) on a rubbery polyisoprene. When the thickness of the upper PMMA film fell short of a threshold value of 50 nm, the adhesion of fibroblasts on it was remarkably suppressed. A possible explanation is that the surface of a bilayer with an ultrathin PMMA layer apparently becomes softer due to the manifestation of a mechanical response from the rubbery layer underneath. Finite element analysis shows that the shear stress at the bilayer surface induced by traction force of the attached cells is dependent on the PMMA thickness, similar to the cell adhesion behavior. These results make it clear that fibroblasts can sense the surface stiffness of polymers with a modulus even on the order of MPa.